THE PRESENCE OF ANOTHER-NATIVE IN LAS COMARCAS (1964) OF JUAN GONZALO ROSE - Uceda Paredes, Amer Sebastián (2019)
In this article it is argued that the poetry book Las comarcas (1964) by Juan Gonzalo Rose evidences the trip of a subject in search of a non-Western rationality, linked to the natives of the tropical zones. In addition, through an interdiscursive analysis, some important themes of the chosen texts are highlighted, such as irony and the representation of ancient knowledge. Likewise, Rose's poems are compared with those of Antonio Cisneros and Rodolfo Hinostroza.